GIS APPLICATION FOR EVALUATION OF TRADE AND SERVICES AREA DEVELOPMENT IN SERANG CITY, BANTEN PROVINCE - Aji, Adam Hastara; Rachmita, Nurina; Sari, Nurwita Mustika; Kushardian, Benedictus (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
Trade and service area is an area that facilitates trade transactions and services between people in need (demand side) and people who sell services (supply-side). In determining trade areas and services, SMCE or Spatial Multi-Criteria Evaluation or spatial evaluation techniques consider many different criteria when making decisions. The method used in this paper is SMCE with Weight Overlay technique using four variables, namely roads, slopes, settlements and rivers. Weighting carried out in the analysis was made with various simulations, namely Simulation A with the same weight weighting on each variable 25%, simulation B with dominant weighting on one of the variables with a composition of 55%:15%:15%:15% and simulation C gave the highest weight to the most influential variables and gave the lowest weight to the variables that were less influential for the Trade and Service Area. In this Simulation, the road network's weight is 30%, settlements are 25%, slopes are 25%, and the rivers are 20%. The total area of 23.5 Km2 or about 8.8% of Serang City area located in the city centre with excellent accessibility, not far from residential areas, a safe distance from the river, and an area with flat marbles.